DEVELOPING HISTORY SUBJECT ON CHALLENGE BASED LEARNING TO PROMOTE HISTORICAL THINKING SKILLS - Ketrattanamalee, Kirati; Pana, Supanut; Thaijongrak, Nathaporn (Journal of Educational Review Faculty of Education in MCU, 2025)
This research aims to: 1) develop a history subject based on the challenge-based learning approach to promote historical thinking skills, and 2) compare students’ historical thinking skills before and after implementing the challenge-based learning approach. This study employs a developmental research design, with a sample group of 30 ninth-grade students in the 2024 academic year, selected using purposive sampling method. The research process consists of two phases: (1) developing the history subject using the challenge-based learning approach to enhance historical thinking skills, and (2) implementing and testing the learning model. The research instruments consist of a lesson plan based on the challenge-based learning approach, parallel tests for assessing historical thinking skills—Set 1 (pre-test) and Set 2 (post-test)—and a historical thinking skills evaluation form. The collected data were analyzed using content analysis, followed by a comparison of students’ historical thinking skills before and after the experiment using mean, standard deviation and dependent t-test. The research findings reveal that: 1) the challenge-based learning approach for promoting historical thinking skills consists of principles of learning, instructional preparation, and a five-step teaching process: (1) Big Idea, (2) Essential Question, (3) The Challenge, (4) Solution, (5) Assessment, along with measurement and assessment methods. 2) Students who engaged in challenge-based learning demonstrated significantly higher historical thinking skills after the experiment at the .05 significance level. Specifically, students were able to formulate questions, seek information, evaluate source credibility, and analyze historical events, indicating an enhancement of their historical thinking skills.